PENGARUH METODE DOUBLE MOVEMENT TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN AL-QUR’AN DAN HADITS - Ulfa Kesuma; Fitri Oviyanti; Mardeli Mardeli (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2019)
The Double Movement Method is a way of interpreting the Qur'an that is taken through two movements (steps). The first step, one must understand the meaning or meaning of a statement by examining the historical situation or problem in which the Qur'anic statement is the answer. The second step is to generalize those specific answers and declare statements that have moral-social goals. Al-Qur'an subjects Hadith are important subjects relating to the study of the legal basis and rules in carrying out religious life. The importance of studying and practicing the Qur'an and Hadith so that it is formed into a Muslim person. This study aims to find out how the double movement method in MTs N 1 Palembang, how student learning outcomes in the Al-Qur'an Subjects and Hadith in MTs N 1 Palembang, is there any influence of the double vovement method on student learning outcomes in Al-Qur'an subjects 'an and Hadith in MTs N 1 Palembang. This research is included in a quantitative field research that uses simple statistical analysis techniques, namely using the percentage formula and product moment analysis techniques. The sample in this study was class VII, amounting to 345 students taken by the Random Sampling technique, the sample amounted to 35 students. While the data collection in this study uses the method of observation, questionnaires, and documentation. The results of this study can be seen in the data analysis namely the correlation value of rxy calculation of 0.78 the correlation index number obtained is not negative, it can be said that there is a significant influence between the variable x and y, then the rxy obtained is 0.78 located between 0, 70-0.90. Based on the above calculation, α = 0.05 and n = 35, one-party test: Dk = n - 2 = 35-2 = 33 so that a table = 1.692 is obtained. It turns out that tcount>ttable is 5.72> 1.692, then H0 is rejected, meaning that there is a significant influence between the Double Movement Method and Student Learning Outcomes in the subject of al-Qur'an hadith in MTs N 1 Palembang.